Evolutionary game and numerical simulation of participants' collaborative behavior in integrated project delivery project - Kai Liu; Yufeng Liu; Hongmin Zhou; Yuanyuan Kou; Qiang Ji; Dan Li (Alexandria Engineering Journal, 2021)
BIM cost, owner's punishment intensity, liquidated damage, size and allocation ratio of incentive pool, Integrated Project Delivery (IPD) gain, loss caused by BIM data resource sharing and other variable parameters are introduced into tripartite evolutionary game model which is established based on evolutionary game theory. Tripartite behavioral strategies are analyzed by evolutionary game theory. The stability of system equilibrium and influence of variable parameters on the stability of evolutionary games are discussed. The tripartite dynamic evolutionary game law based on collaborative behavior under the premise of limited rationality is studied. Then, the tripartite game pathways are numerically simulated by using MATLAB software. The influence of initial intention and variable parameters on the process and results of system evolution are analyzed. The dynamic mechanism of owner's supervision on contractor's and designer's collaborative behavior strategies is clarified. It shows that key point of driving participants to choose collaborative behavior is on owner side.